The history of the Belarusian-Chinese cooperation in the field of tourism in 2013–2020 - Gaidukevich, Leonid M. (Journal of the Belarusian State University. History, 2021)
The article examines the history of the formation of cooperation between Belarus and China in the field of tourism in the newest period of development in the context of the intensification of the Belarusian-Chinese interaction in general. The main tendencies of cooperation within the framework of the global Chinese project «One belt, one road» are outlined, the main tendencies of such cooperation and its specificity, including tourism sphere, are outlined; the main problematic issues in organising tourist exchange with the China are identified.
Keywords: «One belt, one road» project; GDP growth rates; investments; tourism; tourist services; visa-free policy; pandemic COVID-19; integration unions and associations